Microstructural analyses of artificial ageing in 5 commercially and non-commercially available Zirconia dental implants. Issue 10 (August 2020) - Monzavi, Mona; Zhang, Fei; Douillard, Thierry; Gremillard, Laurent; Noumbissi, Sammy; Nowzari, Hessam; Chevalier, Jerome
Abstract: Objectives: The present in vitro study evaluated the effect of LTD (Low Temperature Degradation) on microstructural properties, phase transformation and micro-crack formation of 5 commercially and non-commercially available Zirconia dental implant systems. Methods: Accelerated ageing at 134 °C and 2 bar pressure for 30 h was completed. Focused Ion Beam-Scanning Electron Microscopy (FIB/SEM), X-ray diffraction (XRD) and cathodoluminescence quantified phase transformation and micro-crack formation. Results: Transformation of the tetragonal grains towards the monoclinic symmetry was observed in all systems. The highest depth was measured in non-commercial TAV dental with the largest grain size (8.7 μm). A micro-cracked layer was associated with the transformation zone. The ageing-related micro-crack formation was parallel to the surface for all groups and was deepest for the non-commercial TAV dental with the largest grain size (7.4 μm). Conclusion: LTD following in vitro ageing using an autoclave was minimal for all implant systems investigated.